Improving Arabic Speaking Proficiency (Muhādatsah) Using Interactive-Communicative Instruction - Maryani, Novy; Syafei, Isop; Kosim, Abdul (UIN Sunan Gunung Djati Bandung, 2024)
This research delves into the efficacy of interactive-communicative learning methodologies in enhancing Arabic speaking proficiency, particularly within the realm of Muhādatsah (conversation). Interactive-communicative learning underscores direct learner interaction, fosters active communication, and furnishes an authentic educational environment. It is a potentially superior alternative to conventional learning techniques for bolstering Arabic speaking proficiency. The research amassed qualitative and quantitative data through classroom observations, interviews, and speaking proficiency assessments. Participants, comprising students with varying degrees of Arabic speaking skills in a tertiary education setting, were segmented into two groups: an experimental cohort exposed to interactive-communicative learning and a control cohort following traditional pedagogical approaches. The outcomes evinced a marked enhancement in Arabic speaking proficiency among learners engaging with interactive-communicative instruction vis-à-vis the control group. Those in the experimental cohort exhibited more pronounced advancements in vocabulary acquisition, sentence construction, and oral fluency, alongside a heightened confidence in Arabic communication. These findings suggest that interactive-communicative learning holds promise as a pragmatic strategy for ameliorating Arabic speaking aptitude. They underscore the significance of integrating genuine, contextualized learning experiences to facilitate learners' linguistic competence development. Subsequent research endeavors could explore techniques to enhance the efficacy of interactive-communicative learning within Arabic language education contexts.